2021
DOI: 10.1111/fcp.12716
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cannabinoid receptor 2 (CB2) limits collagen production—An in vitro study in a primary culture of human fibroblasts

Abstract: Previous studies showed that cannabinoid 2 (CB2) receptor is involved in skin inflammation, fibrogenesis and re-epithelialization in mice, indicating that this receptor may be implicated in wound healing. Thus, topical use of cannabinoids may have a role in local fibrotic and wound healing diseases such as scars or keloids. We investigate the effect of the CB2 selective receptor agonist (6aR,10aR)-3-(1,1-Dimethylbutyl)-6a,7,10,10a-tetrahydro-6,6,9-trimethyl-6H-dibenzo[b,d]pyran (JWH133) and the CB2 selective r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…When the fibroblasts were not treated with TGF‐β, only AM630 led to decreased collagen deposition and α‐SMA expression. This study showed the complex interplay of CB 2 on the wound healing process 51 …”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…When the fibroblasts were not treated with TGF‐β, only AM630 led to decreased collagen deposition and α‐SMA expression. This study showed the complex interplay of CB 2 on the wound healing process 51 …”
Section: Resultsmentioning
confidence: 65%
“…This study showed the complex interplay of CB 2 on the wound healing process. 51 Styrczewska et al 22 performed scratch test assays with hydrophobic flax fiber extract, which contained CBD, and demonstrated improved wound healing via inhibition of chronic inflammation and promotion of extracellular matrix remodeling and skin cell migration. The authors suggested the improvement is secondary to two components: presence of CBD and the content of phytosterol.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Another investigation showed that cannabinoid CB 2 receptors are upregulated in neutrophils, macrophages and myofibroblasts in a time-dependent manner during skin wound healing in mice [ 175 ]. Moreover, a recent study using primary cultures of adult human fibroblasts revealed that TGF-β, a profibrotic mediator, significantly increases the expression of CB 1 [ 176 ] and CB 2 receptors [ 177 ], suggesting that both receptors may play a role in fibrotic diseases of the skin and thus represent potential targets for pharmacotherapeutic interventions. Moreover, in mice in the above-mentioned model of streptozotocin-induced type 1 diabetes associated with accelerated skin ageing, the CB 1 receptor has been shown to be downregulated, which was accompanied by higher expression of pro-inflammatory markers [ 166 ].…”
Section: The Endocannabinoid System In the Skinmentioning
confidence: 99%
“…Under the same experimental conditions, the authors also found that the CB 2 receptor agonist JWH-133 decreased α-SMA expression and collagen content in TGF-β-stimulated cells, but not in resting cells. On the other hand, the CB 2 receptor antagonist AM-630 also decreased α-SMA expression and collagen content in both resting and TGF-β-stimulated cells, but at higher concentrations (≥3 µM) [ 177 ]. The authors concluded that the effects produced by JWH-133 show potential for the treatment of hypertrophic scars or keloids in humans.…”
Section: Selected Skin Diseases—pharmacotherapy and Effect Of Cannabi...mentioning
confidence: 99%
“…Nevertheless, downregulation of α-SMA continues to be frequently utilized as a surrogate for antifibrotic activity in analysis of novel keloid therapies. [25][26][27][28][29][30][31] Given the emphasis on reduction of α-SMA-expressing myofibroblasts as a therapeutic endpoint, it is important to critically examine the role and presence of myofibroblasts in keloid pathology. We previously performed gene expression profiling of keloid fibroblasts and failed to detect increased expression of ACTA2, the gene encoding α-SMA, compared with normal fibroblasts.…”
Section: Introductionmentioning
confidence: 99%